2013
DOI: 10.4103/2231-0762.115715
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and treatment needs among 12- and 15-year-old government and private school children in Shimla city, Himachal Pradesh, India

Abstract: Objectives:To assess the dental caries, periodontal health, and malocclusion of school children aged 12 and 15 years in Shimla city and to compare them in government and private schools.Materials and Methods:A cross-sectional study of 12- and 15-year-old children in government and private schools was conducted in Shimla city, Himachal Pradesh, India. A sample of 1011 school children (both males and females) was selected by a two-stage cluster sampling method. Clinical recordings of dental caries and malocclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 15 publications
1
17
3
Order By: Relevance
“…Most of them (78%) used to brush once a day which is in line with the findings of shailee et al, [7] but high as compared with findings of Harikiran and Pallavi [8] and Peng et al, [9], where as only 21.3% of student brushed twice daily which is low. The fact that all the children examined belong to government school and most of them come from illiterate-low socio-economic families is responsible for this finding.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Most of them (78%) used to brush once a day which is in line with the findings of shailee et al, [7] but high as compared with findings of Harikiran and Pallavi [8] and Peng et al, [9], where as only 21.3% of student brushed twice daily which is low. The fact that all the children examined belong to government school and most of them come from illiterate-low socio-economic families is responsible for this finding.…”
Section: Discussionsupporting
confidence: 76%
“…• Regular interval screening programs to assess the oral health and treatment needs of school children and provision of treatment as per the need [7].…”
Section: Discussionmentioning
confidence: 99%
“…23 Also the teachers' training programs can ensure continuity of reinforcement. School dental health programs focusing on preventive and toothbrushing programs including fluoride mouth rinse should be implemented.…”
Section: Resultsmentioning
confidence: 99%
“…15,19 Similar to this study, another research showed a statistically significant difference in decayed, missing, and filled teeth (DMFT) scores between the private and government school children. 16 The prevalence of dental caries among 12-year-old children from private schools and government schools was 32.8 and 70.3% respectively. Poor oral health of public and rural schoolchildren was attributed to lack of awareness, lack of affordability, or underutilization of dental care facilities by the children in government schools.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Oral health is influenced by several social, economic, and environmental factors, which play a vital role in shaping positive oral health behavior. 18 Several researches have revealed that oral health of private schoolchildren is better than public school and rural school because of following reasons: private schoolchildren belong to higher socioeconomic status; have more affordability; parent's attitude; dental awareness, and better social support.…”
Section: Discussionmentioning
confidence: 99%